The Association between Waist Hip Ratio and Severity of Diabetic Peripheral Neuropaty in Diabetes Melitus Type 2 by Using Toronto Clinical Scoring System - Dhillon, Sharanjit; Fithrie, Aida; Batubara, Chairil Amin (Journal of Society Medicine, 2023)
Introduction: Diabetic neuropathy is a common and progressive microvascular complication of diabetes, so early detection and prevention is very important. Other modifiable risk factors such as hypertension, dyslipidemia, or central obesity can be managed. Central obesity with insulin resistance is a key pathophysiological factor in the metabolic syndrome. Waist hip ratio (WHR) has been proposed as a tool for detecting central obesity. Toronto Clinical Scoring System (TCSS) is a diabetic neuropathy scoring system that has high sensitivity and specificity. The aim of this study was to determine the relationship between waist hip ratio and the severity of peripheral diabetic neuropathy in type 2 Diabetes Melitus (DM) according to the Toronto Clinical Scoring System (TCSS). Method: This study used a cross-sectional design. Sampling was conducted at the Endocrinology Polyclinic and Neurology Polyclinic Hospital H. Adam Malik Medan. The research sample was taken as many as 45 subjects consecutively. TCSS examination is performed to diagnose and determine the severity of diabetic neuropathy Therefore, waist hip ratio was calculated to assess central obesity. Data analysis using Chi Square test. Results: On the demographic characteristics of the research subjects were male, age range 51-60 years, high school education level, not working, history of DM 5-10 years. The mean value of WHR is 0.87±0.051. Median TCSS Score 10 (6-16). The majority of subjects had mild diabetic peripheral neuropathy. Patients with central obesity had a grading of neuropathy that was classified as severe as many as 13 people (56.5%), moderate as many as 7 people (30.4%), and mild as many as 3 people (13.0%). While patients who are not obese have a grading of neuropathy that is classified as severe as many as 1 person (4.5%), moderate as many as 5 people (22.7%), mild as many as 16 people (72.7%). Based on the Chi Square test, it was found that there was a significant association between the waist hip ratio and the severity of diabetic peripheral neuropathy in type 2 DM patients with p<0.01. Conclusion: There is a statistically significant association between waist hip ratio and the severity of diabetic neuropathy in type 2 DM with p < 0.01.